LENGTH - WEIGHT RELATIONSHIP OF TWO PALAEMOID PRAWNS , MACROBRACHIUM IDELLA AND M. SCABRICULUM - A COMPARATIVE STUDY - JAYACHANDRAN, K V; JOSEPH, N I (Fishery Technology, 2017)
Length-weight relationships of two commercially important freshwater prawns, Macrobrachium idella and M. scabriculum, have been worked out separately for the two sexes of the two species. 't' test showed that growth departs significantly from the isometric growth in the case of both sexes of M. idella and in the female of M. scarbriculum. Therefs re, the cubic formula W = CL 3 may be applied only in the case of males of M. scabriculum. In all the other cases W = CLD may be followed.